2019
DOI: 10.1088/1741-4326/ab5e64
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion characterization in a helicon plasma source for fusion neutral beams by cavity ring-down spectroscopy and Langmuir probe laser photodetachment

Abstract: Negative ions are characterized in the helicon plasma source RAID (Resonant Antenna Ion Device) at the Swiss Plasma Center by means of Cavity Ring-Down Spectroscopy (CRDS) and Langmuir Probe (LP)-assisted laser photodetachment. A high density and axially homogeneous plasma column is produced via a RF antenna able to sustain the propagation of helicon waves in a steady state regime. An electron density n e ∼ = 2.0 × 10 18 m −3 in H 2 plasma at 0.3 Pa and 3 kW of input power is measured in the center of the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 35 publications
(77 reference statements)
3
27
0
Order By: Relevance
“…In this work, the unique combination of a SR source and Vacuum Ultra Violet Fourier Transform Spectrometer (VUV-FTS) allows a direct and accurate measurement of the density of the ro-vibrationnal components of the D 2 molecule in its ground state. Recent results have shown that a caesium-free (Cs-free) Helicon plasma reactor, named RAID, produces at 3 µbar and 5 kW a negative ion density of ∼ 2 × 10 16 m −3 in H 2 plasma and ∼ 1.75 × 10 16 m −3 in D 2 plasma 75 . In comparison with BATMAN 25 ion source, the one eighth scale prototype of the future negative ion source of ITER tokamak, the same density of H − is obtained with an input power of 40 kW when using caesium 76 .…”
Section: Many Authors Have Used Laser-based High Resolution Methods To Perform Direct Measurements Of V Densitiesmentioning
confidence: 99%
“…In this work, the unique combination of a SR source and Vacuum Ultra Violet Fourier Transform Spectrometer (VUV-FTS) allows a direct and accurate measurement of the density of the ro-vibrationnal components of the D 2 molecule in its ground state. Recent results have shown that a caesium-free (Cs-free) Helicon plasma reactor, named RAID, produces at 3 µbar and 5 kW a negative ion density of ∼ 2 × 10 16 m −3 in H 2 plasma and ∼ 1.75 × 10 16 m −3 in D 2 plasma 75 . In comparison with BATMAN 25 ion source, the one eighth scale prototype of the future negative ion source of ITER tokamak, the same density of H − is obtained with an input power of 40 kW when using caesium 76 .…”
Section: Many Authors Have Used Laser-based High Resolution Methods To Perform Direct Measurements Of V Densitiesmentioning
confidence: 99%
“…If the negative ion to electron n i -/n e density ratio is considered, results obtained at similar plasma conditions and position in PROMETHEUS-I reactor (see Sect. 3.1) [67] (a network of five identical ECR dipolar sources) and in the RAID reactor [76] are comparable: 0.18 and 0.225, respectively. In consequence, the plasma features, produced by an ECR dipolar source, can be considered similar enough to the one obtained in the RAID reactor to allow an investigation of the ECR plasma rather than the helicon plasma when plasma diagnostic cannot be set up for RAID.…”
Section: Experimental Investigation On Recombinative Desorption Mechanism In An Ecr (245 Ghz) Plasmamentioning
confidence: 96%
“…2.2.1 Dipolar plasma source to scrutinize the production of ro-vibrationally excited molecules at lower scale Actual neutral beam injector (NBI) design shows a global efficiency below 50% (The total or global efficiency of the injector, called wall-plug efficiency is the ratio of the neutral power at the entrance of the tokamak and the total electric power consumed in the injector (ion source + accelerator + recovery electrode + auxiliary systems). A higher aspect ratio (height over width) could increase the efficiency to more than 60% [76]. In particular, the photoneutralization could be employed on blade-like beams.…”
Section: Experimental Investigation On Recombinative Desorption Mechanism In An Ecr (245 Ghz) Plasmamentioning
confidence: 99%
See 2 more Smart Citations